Pathologic findings of the placenta and clinical implications – recommendations for placental examination (Swiss Medical Weekly, 2024)
The placenta is a unique and complex organ that combines the circulatory systems of two or more individuals within a single dynamic organ with a set, short lifespan. A diverse spectrum of disorders, including infections as well as metabolic, genetic, circulatory, and maturation defects, may affect its function. Pathology investigation of the placenta is key for identifying several pathogenic processes in both the mother and the foetus. Aberrant placentation, maternal and foetal vascular compromise, infection, inflammatory immunologic conditions, and disorders of maturation are elements of newly proposed classification schemes.The clinical impact of placental examination consists of diagnosing maternal and foetal disease, identifying the potential for recurrence, correlating clinical pathological findings with distinct morphologic features, and identifying the aetiology responsible for growth restriction or foetal death.Gestational trophoblastic disease occurs more frequently in the first trimester; however, in very rare cases, it can affect the term or third-trimester placenta.The application of reproducible nomenclature is expected to facilitate progress in the diagnosis and treatment of obstetric and foetal disorders with placental manifestation.Therefore, this review aims to facilitate communication between obstetricians, neonatologists, and pathologists involved in this diagnostic process.